The Book by an American Scholar on "The Man in the Panther Skin" - Elguja Khintibidze; Gvantsa Tcholikauri (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2014)
Based on the latest research by an American scholar, Dianne Farrell, this article discusses several Issues relating to the manifestation of the concept of love in The Man in the Panther Skin in contrast with the concepts of love as expressed in Oriental epic and Western courtly love.